Determinants of Board Size and Its Composition: Evidence from Nigerian Manufacturing Sector - Mustapha Y. I.; Nafiu A. I.; Abdul F. A.; Omolekan, O. J. (Kelaniya Journal of Management, 2020)
This paper examines the determinants of corporate board size and its composition in Nigeria using listed manufacturing firms as study area. The objective of the paper is to determine the effect of firms’ characteristic on board size. The study collected secondary information from thirty listed manufacturing firms that met the requirement for selection as sample between 2006 and 2018 through Nigerian Stock Exchange’s Fact Books. Multiple regression analysis was used as analytical technique. Using panel data OLS pooled method of estimation, the paper found that firm size, profitability, and growth opportunities are strong determinants of board size. Similarly, the results indicated that CEO-duality and profitability were determinants of board composition in the study. It is recommended that appointment into corporate board should be based on proven demonstration of high level of expertise, merit and due consideration to firms’ characteristics instead of mundane factors that would not enhance shareholders’ wealth.